Toluene steam reforming over nickel based catalysts. (13th May 2021) - Sayas, S.; Vivó, N.; Da Costa-Serra, J.F.; Chica, A.
Abstract: Steam reforming of toluene (SRT) has been studied initially in eight nickel-based catalysts where nickel (10 wt%) was incorporated in different supports (olivine, Al2O3, MgO, LDH, ZrO2, CeO2 and natural sepiolite) by the incipient wetness impregnation method. Among them, nickel catalyst based on sepiolite exhibited a promising catalytic performance, with a high conversion of toluene (16%), high selectivity to hydrogen (68.4%) and low production of undesired by-products (CO, CH4, ethylene and benzene) at low temperature (500 °C). On the other hand, the incorporation of Ni in the sepiolitic material by precipitation (PP) has been considered as alternative method to the incipient wetness impregnation method (IWI). PP method allowed to prepare a Ni-based catalyst with a very high activity (conversion of toluene ~100%), high selectivity to hydrogen (73%) and lower production of undesirable by-products (5% CO, 2% CH4 and 0% C6 H6 ) at 575 °C. In addition, catalytic deactivation due to coke deposition and nickel sinterization was clearly lower for the catalyst synthesized by PP. Characterization by different physicochemical techniques (XRD, TEM, BET surface area, ICP-OES, TPR and EA) showed that PP method allowed to obtain a sepiolite-based catalyst containing Ni with larger external surface area and smaller, highly dispersed and easily reducible Ni metal particles. The results here discussed show that the Ni incorporation method has a clear influence in the preparation of nickel catalyst supported on sepiolite with improved catalytic performance in the steam reforming of toluene. Highlights: Eight supports with Ni have been tested in the steam reforming of toluene. High Toluene conversion and H2 selectivity is exhibited by sepiolite-based catalyst. IWI and PP methods to incorporate Ni in the sepiolitic support has been studied. 10NiNS (PP) has the best catalytic performance with high stability. Small size and high dispersion and reduction degree explain the excellent results.